Spatiotemporal Environments – Translations of Workers Narratives into Visual Texts - Sinfield, D (Common Grounds, 2011)
The International Conference on Interdisciplinary Social Sciences examines the nature of disciplinary practices, and the interdisciplinary practices that arise in the context of ‘real world’ applications. It also interrogates what constitutes ‘science’ in a social context, and the connections between the social and other sciences. In this project and conference presentation it moves concerns with narratives of underpaid work into spatiotemporal environments. Audio recordings of worker’s stories are fused with typographical treatments and imagery to produce a series of short films. The advantage of this approach is that these texts are more widely available and operate outside of the cultural exclusivity of the art gallery and the graphic design field. This is an international conference that has been running for 6 years which is organised by Common Ground Publishing. Each year this conference is held in various countries throughout the world and this year it will be held in New Orleans, USA. Speakers are also invited to publish their journal article (which is peer reviewed) with the publication associated with this conference.